A smartphone-based exercise adherence intervention for people with metabolic syndrome: a feasibility pilot study. (October 2016) - Sit, Janet WH; Chair, Sek-Ying; Hui, Stanley SC; Choi, Kai-Chow; Chan, Aileen WK; Wong, Eliza ML; Cheng, Ho-Yu
Abstract: Background: Despite well-established benefits of exercise in the management of metabolic syndrome, evidence to support exercise adherence after program completion is lacking. We used a smartphone-based exercise adherence intervention (Virtual Trainer; Ex-VT) for adults with metabolic syndrome in Hong Kong, China. The objectives were to measure the feasibility, potential effectiveness, and implementation of Ex-VT in sustaining prescribed exercise practice for risk reduction in metabolic syndrome. Methods: In this multisite, randomised controlled trial, participants with metabolic syndrome were randomly allocated to either intervention (Ex-VT) or exercise reference (control) groups using block randomisation with a block size of ten. Both groups attended four once-weekly group exercise sessions. The Ex-VT group received goal-directed, person-centered exercise adherence coaching via a smartphone virtual trainer application. Data was collected at baseline and at 12 weeks. Primary outcome was adherence to exercise prescription, as measured using pedometers and International Physical Activity Questionnaire. Changes in metabolic syndrome risk indicators (waist circumference, blood pressure, and blood lipid and glucose concentrations) were also measured after a 12 h fast. Data analysis was based on intention to treat. The trial is registered with Chinese University of Hong Kong Centre for Clinical Research and Biostatistics, number CUHK_TMP00056. Ethics approval was obtained from the Joint Chinese University of Hong Kong–New Territories East Clinical Research Ethics Committee and written consent were obtained from participants. Findings: Twenty subjects were recruited to the study (recruitment rate: 71·4%), and randomly assigned, 1:1, to Ex-VT or control groups. They were aged 30–69 (mean 56·85 [SD 7·08]), 65% women, and 55% worked full-time. Two subjects (one per group) dropped out (retention rate: 90% for both groups). At 12 weeks, participants in the Ex-VT group demonstrated better adherence with exercise prescription (72%) than those in the control group (48%; p=0·036). Reductions from baseline in systolic blood pressure (p=0·02), diastolic blood pressure (p=0·045), and waist circumference (p=0·048) were seen in the Ex-VT group, despite no between-group difference. We found no significant changes in blood lipid and glucose concentrations. No adverse events were reported. Interpretation: High retention rates suggest that Ex-VT is an acceptable intervention for this population. Preliminary findings on adherence and metabolic syndrome risk indicators suggest that a large randomised controlled trial to explore the effects of Ex-VT would be safe, feasible, and warranted. Funding: Departmental Research Fund, Cardiac and Acute Care Research Theme Group, The Nethersole School of Nursing, Faculty of Medicine, Chinese University of Hong Kong, Hong Kong, China (CV1502).